Comparative Analysis of the Impact of Training on Microenterprise Development in Sidoarjo Regency - Virdean Paulia Pratama; Sri Wibawani; Erwing Wahyu Millensyah (Journal of Government and Politics (JGOP), 2025)
The growth of micro enterprises in Sidoarjo Regency is a positive phenomenon, driven by an increase in community initiatives to establish independent businesses. However, this growth needs to be accompanied by the government's active involvement in enhancing the capacity of micro-enterprises through targeted programs or policies. One such effort is reflected in the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 18 of 2015, which provides guidelines for education and training aimed at developing the human resources of cooperatives as well as micro, small, and medium enterprises. In line with this regulation, the Office of Cooperatives and Micro Enterprises has provided a digital marketing training program. Nevertheless, micro-entrepreneurs still face challenges, such as a limited understanding of digital technology. Therefore, it is necessary to measure the extent to which the provided training can impact micro enterprises productivity and capabilities. This research is intended to investigate significant differences in the impact of micro enterprises development training in Sidoarjo Regency. This study employs a quantitative approach with a comparative design using a one-group pretest-posttest method. Data were collected using a questionnaire distributed to 100 respondents. The data were analyzed using a paired t-test with SPSS Version 30. The findings revealed a statistically significant difference in the impact of micro enterprises development training in Sidoarjo Regency (t(99) = -17.606, p < 0.001). These results indicate that the training program positively impacts micro enterprises development in Sidoarjo Regency.